2019
DOI: 10.1002/adfm.201907562
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Flexible Hybrid Membranes with Photonic Structures for Daytime Radiative Cooling

Abstract: Passive radiative cooling technology can cool down an object by reflecting solar light and radiating heat simultaneously. However, photonic radiators generally require stringent and nanoscale-precision fabrication, which greatly restricts mass production and renders them less attractive for large-area applications. A simple, inexpensive, and scalable electrospinning method is demonstrated for fabricating a high-performance flexible hybrid membrane radiator (FHMR) that consists of polyvinylidene fluoride/ tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
206
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(206 citation statements)
references
References 38 publications
0
206
0
Order By: Relevance
“…The introduction of polymer-based radiative cooling materials can greatly improve the scalability and applicability of PDRC systems in practical applications 18 , 30 33 . Very recently, instead of using a reflective metallic mirror, state-of-the-art PDRC designs, such as porous polymer coatings 17 , 34 , 35 , polymeric aerogels 36 , white structural wood 37 and cooling paints 38 , 39 , have attracted considerable attention because of their high cooling performance, simplicity, applicability and economical efficiency. For example, Yu et al 17 made remarkable progress in the design of PDRC poly(vinylidene fluoride-co-hexafluoropropene) coatings with random micro-/nano-pores through a phase inversion-based method, demonstrating high solar reflectance (0.96 ± 0.03), as well as high longwave infrared emittance (0.97 ± 0.02) that enabled cooling up to ~6 °C and ~3 °C below ambient temperature under direct sunlight in dry southwestern USA and south Asia, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of polymer-based radiative cooling materials can greatly improve the scalability and applicability of PDRC systems in practical applications 18 , 30 33 . Very recently, instead of using a reflective metallic mirror, state-of-the-art PDRC designs, such as porous polymer coatings 17 , 34 , 35 , polymeric aerogels 36 , white structural wood 37 and cooling paints 38 , 39 , have attracted considerable attention because of their high cooling performance, simplicity, applicability and economical efficiency. For example, Yu et al 17 made remarkable progress in the design of PDRC poly(vinylidene fluoride-co-hexafluoropropene) coatings with random micro-/nano-pores through a phase inversion-based method, demonstrating high solar reflectance (0.96 ± 0.03), as well as high longwave infrared emittance (0.97 ± 0.02) that enabled cooling up to ~6 °C and ~3 °C below ambient temperature under direct sunlight in dry southwestern USA and south Asia, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As an innovative and environmentally friendly alternative, the recently emerged passive radiative-cooling materials can be used for achieving energy-efficient buildings (2,3), efficient solar cells (4,5), novel cooling fabrics (6)(7)(8)(9), and supplemental cooling systems for power plants (10,11). The key to achieve a lower temperature than that of the surroundings even under direct sunlight is to have a high reflectivity to repel incoming sunlight (wavelength 0.3 to 2.5 μm) and a high thermal emissivity to radiate heat to outer space in the transparent atmospheric spectral window (TASW; 8 to 13 μm) (12)(13)(14)(15)(16)(17). In recent years, there have been several proposals and demonstrations of photonic structures for controlling both solar reflection and thermal emission by manipulating light-matter interactions at subwavelength scales (18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…It is observed that silicon dioxide nanoparticle dispersed in polymer alone not sufficient to reflect as desired in the solar spectrum and alternate structure with particle and void may lead to optimum results. SiO 2 nanoparticle on the surface of polymer with numerous void inside reflects 97% solar spectrum and creates a flexible material for broad ranges of applications 29 . The difference in cooling power raises 6–17 W/m 2 for a 15 °C rise in the temperature of two extreme performance nanoparticles.…”
Section: Resultsmentioning
confidence: 99%